Implementación del primer laboratorio integral para la restauración del patrimonio cinematográfico en el Perú: el rol de la Asociación Guarango Cine y Video - Rebata Delgado, Sofía Magaly (2024)
The essay analyzes the process of implementation of the first integral restoration laboratory by Guarango Film and Video Association (Guarango) in Peru. This milestone is based on a culture of research, innovation, continuous training, and effective fund management. It highlights Guarango’s commitment to the enhancement of film heritage and the development of the national film industry. It examines the state of regional film heritage, Guarango’s experience as an organization, its high-quality productions, and technological advances. It also details the restoration process, quality control and laboratory equipment. The case of Guarango represents a significant advance for the film industry, standing out as an example of commitment to the preservation of audiovisual heritage and the promotion of national cinema.